The application of entrepreneurship in law based on 1014 2006 su percentage of spending in the public sector and state aid (2013)
Applying Entrepreneurship and thus the creation of Business is one of the largest engines that contribute to the Economic and Social development of the country under the law marked 1014 2006 Where the Company aims to generate wealth as they are exporting and importing, that through these commercial and operational exchange between Countries Facing the challenges facing Colombia to the Phenomenon of Globalization and Economic integration is energized. It is necessary to analyze the Entrepreneurship Policy seeks to develop actions that facilitate entrepreneurship where the premise is to foster an entrepreneurial climate that fosters creativity and innovation in young people and children in school and university stages in order to achieve a dynamic increased economic activity grounded in the business and participatory foundations of Public, Private and Educational sectors.